Software defined wireless networks with real-time constraints - Llinas, Andres; Micheletto, Matias; Santos, Rodrigo; Ochoa, Sergio (Anais do Workshop on Security, Privacy and Reliability on Wireless Sensing Networks (WSENSING); 2023: Anais do III Workshop on Security, Privacy and Reliability on Wireless Sensing Networks, 2023)
Wireless networks have become the main way in which devices connect to Internet. In fact this technology is fundamental for the development of Internet of Things (IoT).Sometimes, applications have real-time requirements adding temporal constraints to the data transmission and putting extra stress on the network messages propagation. In this realm, it is necessary to appeal to dynamic configuration paradigms which allow quickly structuring the operation of the networks, in order to avoid collapses under certain situations during their operation. In this work in progress we propose a software defined networking methodology to handle real-time traffic in wireless networks demands dynamically.Up to the best of the authors knowledge, there is not wide spread accepted mechanism applied to IEEE 802.11 access points programming, and in particular with real-time restrictions.